Interaction between triglyceride-glucose index and thyroid hormones on coronary artery disease risk in patient with euthyroid - Li, Li; Cai, Gaojun; Lu, Wei; Li, Feng; Yu, Lei; Xiao, Jianqiang (Frontiers in Endocrinology, 2023)
Background: Triglyceride glucose (TyG) index is an effective indicator in indentifying in pre-diabetes, diabetes and coronary artery disease (CAD). However, the value of TyG index combined with thyroid hormones(THs) to affect CAD has not been fully evaluated.Here, we investigated the association between TyG index and THs, and further studied the impacts of TyG index and THs on CAD in euthyroid.Methods: 1297 subjects with euthyroid who underwent selective coronary angiography (CAG) were enrolled in the present study, including 893 patients with CAD and 404 controls. The association between TyG index and THs were analysed by linear regression models. Multivariate logistic regression analysis was used to evaluate the interaction of TyG and THs with the risk of CAD. According to the cut-off value of Free Triiodothyronine (FT3), Free Thyroxine(FT4), thyroid-stimulating hormone(TSH) and TyG index, the patients were respectively separated into four groups: low TyG/FT3(low or high), high TyG/FT3(low or high), low TyG/FT4(low or high), high TyG/FT4(low or high), low TyG/TSH(low or high), high TyG/TSH(low or high).The baseline analysis showed that FT4 level differs among the three groups according to the tertile of the TyG index. Multiple linear regression analysis revealed decreased serum FT3 level and sreum FT4 level as an independent risk factor for elevated TyG index. After adjusting for confounding variables, multiple logistic regression analysis showed that patients with lower TyG index and higher FT3 level had an important protective effect on CAD when considering patients with lower TyG index and FT3 level as reference(OR 0.536, 95%CI: 0.369-0.778, P=0.001). Patients with higher TyG index and FT4 level(lower or higher) had a significantly increased risk of CAD (OR 1.656, 95%CI:1.117-2.455; OR 1.920, 95%CI: 1.279-2.848, respectively). The area under the curve for the combined diagnosis of CAD by TyG index and FT3 level is 0.615.Conclusions:These findings suggest that TyG is independently negatively correlated with FT3 or FT4 in euthyroid. In addition, there was a significant interaction between TyG index and THs on the risk of CAD.